Longitudinal pathways of exclusive and polytobacco smokeless use among youth, young adults and adults in the USA: findings from the PATH Study Waves 1–3 (2013–2016). (22nd April 2020) - Sharma, Eva; Edwards, Kathryn C; Halenar, Michael J; Taylor, Kristie A; Kasza, Karin A; Day, Hannah; Gardner, Lisa D; Anic, Gabriella; Bansal-Travers, Maansi; Limpert, Jean; Hammad, Hoda T; Borek, Nicolette; et al.
Abstract : Objective: Use of smokeless tobacco (SLT) with other tobacco products is growing, yet gaps in understanding transitions among SLT and other product use remain. The aim of this study is to examine cross-sectional prevalence and longitudinal pathways of SLT use among US youth (12–17 years), young adults (18–24 years) and adults 25+ (25 years and older). Design: Data were drawn from the first three waves (2013–2016) of the Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal cohort study of US youth and adults. Respondents with data at all three waves (youth, n=11 046; young adults, n=6478; adults 25+, n=17 188) were included in longitudinal analyses. Results: Young adults had the highest current SLT use compared with other age groups. Among Wave 1 (W1) past 30-day youth and young adult SLT users, most were SLT and cigarette polytobacco users compared with adults 25+, who more often used SLT exclusively. Among W1 exclusive SLT users, persistent exclusive use across all three waves was more common among adults 25+, while transitioning from exclusive SLT use to SLT polytobacco use at Wave 2 or Wave 3 was more common among youth and young adults. Among W1 SLT and cigarette polytobacco users, a common pathway was discontinuing SLT use but continuing other tobacco use. Conclusions: Our results showed distinct longitudinal transitions among exclusive and SLT polytobacco users. Deeper understanding of these critical product transitions will allow for further assessment of population health impact of these products.